Plasmon Excitation in BC3 Nanostructures from First Principles - Chen, Jiuhuan; Cheng, Xin-Lu; Zhang, Hong (Plasmonics (Norwell, Mass.), 2019)
The plasmonic of BC3 nanostructure was investigated employing time-dependent density functional theory (TDDFT). What is striking is that BC3 nanostructure possesses preferable absorbance in the visible region. By changing the size of the nanostructure, the resonance peak position of the absorption spectrum can be effectively regulated. Moreover, when excitation direction along the armchair-edge direction, the absorption spectra are clearly stronger in the low-energy zone respect to the impulse excitation polarizes in the zigzag-edge direction. In addition, with the change of layer spacing and number of layers, the resonance frequency and resonance absorption peak intensity of plasmonic can be effectively controlled. The remarkable optical properties of BC3 nanostructure suggest potential application of the system in solar cells and photolysis water devices.